KEKERABATAN BAHASA-BAHASA DI KAWASAN UTARA KABUPATEN JAYAPURA - Suharyanto NFN (Balai Bahasa Provinsi Papua, 2019)
This research aims to know genetic relationship of languages in north area of Jayapura regency, Papua province. Comparative historical theory with quantitative method are used to analyze the languages relationship. The result of analysis shows that eight languages in north area of Jayapura regency do not belong to the same language group. Tevera Pew (Te), Tabla (Ta), Yokari (Yo), and Sentani (St) languages form their own language group as 40,45% cognate words similarity with the name of Tevera Pew-Tabla-Yokari-Sentani. Languages of Tevera Pew-Tabla-Yokari-Sentani derived from Tevera Pew-Tabla-Yokari-Sentani proto. This proto then split to four languages as we found right now. Demta language (De) proven to be out part Tevera Pew-Tabla-Yokari-Sentani language family. Mooi (Mo) and Gresi (Gr) create their own language family with 52,26% similarity of cognate words. Meanwhile, Ormu (Or) and Tarpia (Ta) languages are not belong to any language stock. Ormu (Or) and Tarpia (Ta) only have 9, 28% similarity cognate words. That’s why they do not belong to one language stock.